Meningkatkan Motivasi Siswa Mata Pelajaran Ilmu Pengetahuan Alam dan Sosial Menggunakan Media Wordwall Matchmaking Kelas V Madrasah Ibtidaiyah - Fajarli Fajarli; Vioni Saputri (Guruku: Jurnal Pendidikan dan Sosial Humaniora, 2025)
This research is motivated by the low learning motivation of students, students are not fully involved in the learning process, educators have not yet used more varied learning media in Natural and Social Science learning. The purpose of this study is to increase students' learning motivation in Natural and Social Science subjects using wordwall matchmaking media in grade V of Madrasah Ibtidaiyah Muhajirin Jambi City. This research is a classroom action research consisting of two cycles, each cycle consists of two meetings. Each cycle consists of four stages, namely planning, implementation, observation, and reflection. The subjects of this study are students of Class V Madrasah Ibtidaiyah Muhajirin Jambi City. This research was conducted in the first semester of the 2024/2025 academic year. at Madrasah Ibtidaiyah Muhajirin Jambi City. The results of the data analysis showed that using wordwall matchmaking media can increase students' learning motivation in Natural and Social Science subjects in grade V of Madrasah Ibtidaiyah Muhajirin Jambi City. Details of the results of student observations using wordwall matchmaking media have increased from cycle I to cycle II with an average value of 59.25% with a category of less and increased to 81.25% with a good category. It is concluded that using wordwall matchmaking media can increase students' motivation in Natural and Social Science subjects in grade V of Madrasah Ibtidaiyah Muhajirin Jambi City.